2019
DOI: 10.3329/bjme.v10i1.44589
|View full text |Cite
|
Sign up to set email alerts
|

Socialization of Undergraduate Medical Students in Bangladesh: Students' and teachers' view

Abstract: This descriptive type of cross sectional mixed method study was conducted with four specific objectives to understand the perception, area, ways and barriers in socialization of undergraduate medical students in Bangladesh. The study was conducted in 8 (eight) medical colleges of which 6 (six) are public and 2 (two) are private. The study was conducted for one year from July 2017 to June 2018. Total 712 student of final phase participated in the study. In- depth interview was conducted with teachers. Convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Third step: Sledgehammer's approach We found that, currently, preclinical students are facing two overwhelming stressors. On the one hand, the covid crisis has detached the students from their teachers and resources [15,18,57]. On the other hand, students need to handle their transition into knowledgeable medical professionals.…”
Section: Second Stepmentioning
confidence: 99%
“…Third step: Sledgehammer's approach We found that, currently, preclinical students are facing two overwhelming stressors. On the one hand, the covid crisis has detached the students from their teachers and resources [15,18,57]. On the other hand, students need to handle their transition into knowledgeable medical professionals.…”
Section: Second Stepmentioning
confidence: 99%